(untitled) (Research, Society and Development, 2020)
The objective of this research was to evaluate the efficiency of strains IBCB 425, 348 IBCB, UFGD 22 and UFGD 28 of Metarhizium anisopliae to control Mahanarva fimbriolata, in the culture of sugar cane, in field conditions. The experimental design was a randomized block with five treatments and four replications. Were applied 2 Kg ha-1 of rice + fungus sporulated with a concentration of 1.0 × 10 ¹² viable conidia ha-1. Evaluations were performed at 15, 30, 60, 90, 120 days after application, noting the number of nymphs and adults live, infected and killed not parasitized. It was found that within fifteen days of the treatments were infected insects. There was greater efficiency for IBCB 425 with 72.2% for nymphs and 83.3% for adults. The isolate UFGD 28 promoted the lowest number of nymphs per linear meter (3.7), with an efficiency of 66.3%. In the treatment with the application of the IBCB 425 isolate, 0.7 adults per linear meter and 70.0% efficiency were found, 60 days after spraying. The density of nymphs and adults decreased, 120 days after spraying, remaining below the economic injury level (four nymphs/meter), due to low rainfall in the period. The isolated UFGD 22 had the lowest population of nymphs (1.5) and adults (0.8) per meter, with control efficiency of 85.94 and 75.0% for nymphs and adults, respectively. The isolated IBCB 425 has outperformed causing, on average, 97.98% parasitism for nymphs and 91.3% parasitism for adults, demonstrating the residual power, within 120 days of application.